Біоекологічні особливості малопоширених деревних рослин в умовах південного сходу України - Glukhov, O.Z.; Dovbysh, N.F.; Kharkhota, L.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The data on biological and ecological peculiarities of rare arboreal plants in Ukrainian south-east are given and the possibilities of their accelerated propagation for introduction into green plantings of the region are determined.